Salvia chinensis Benth Inhibits Triple-Negative Breast Cancer Progression by Inducing the DNA Damage Pathway - Wang, Kai-nan; Hu, Ye; Han, Lin-lin; Zhao, Shan-shan; Song, Chen; Sun, Si-wen; Lv, Hui-yun; Jiang, Ni-na; Xv, Ling-zhi; Zhao, Zuo-wei; Li, Man (Frontiers in Oncology, 2022)
Objective: Triple negative breast cancer (TNBC) is distinguished by early recurrence and metastases, a high proclivity for treatment resistance, and lack of targeted medicines, highlighting the importance of developing innovative therapeutic techniques. Salvia chinensia benth (SCH) has been widely studied for its anticancer properties in a variety of cancers. However, its significance in TNBC treatment is rarely discussed. Our present study investigated the anticancer impact of SCH on TNBC, as well as the underlying mechanisms. Methods: First, we used clonogenic assay, cell viability, flow cytometry, and transwell assay to assess the effect of SCH on TNBC. Bioinformatic study, especially network pharmacology-based analysis and RNA sequencing analysis, were performed to investigate the constituents of SCH and its molecular mechanisms involved in the suppression of TNBC. High-performance liquid chromatography and thin-layer chromatography were used to identify two major components, quercetin and β-sitosterol. Then, we discovered quercetin and β-sitosterol's synergistic cytotoxicity and assessed their synergistic prevention of cell migration and invasion. Breast cancer xenografts were also created using MDA-MB-231 cells to test the synergistic therapeutic impact of quercetin and -sitosterol on TNBC in vivo. The impact on the DNA damage and repair pathways was investigated using the comet assay and western blot analysis. Results: Our findings showed that SCH decreased TNBC cell growth, migration, and invasion while also inducing cell death. We identified quercetin and β-sitosterol as the core active components of SCH based on network pharmacology study. According to the RNA sequencing research, the p53 signaling pathway was also regarded as a critical biological mechanism of SCH treatment. The comet assay consistently shown that SCH significantly increased DNA damage in TNBC cells. Our in vivo and in vitro data revealed that the combination of quercetin and β-sitosterol generated synergistic cytotoxicity and DNA damage in TNBC cells. SCH particularly blocked the inter-strand crosslink repair mechanism and the double-strand breach repair caused by the homologous recombination pathway, in addition to inducing DNA damage. Treatment with quercetin and β-sitosterol produced similar outcomes. Conclusion: The current study elucidates a novel insight into a previously unknown therapeutic potential for SCH as a DNA damaging agent in TNBC.